Generative artificial intelligence (ChatGPT) technology and its impact on the development of digital entrepreneurship skills among university students - Abdelmagid, Ahmed Sadek; Jabli, Naif Mohammed; Ibrahim, Asem Mohammed; Teleb, Ahmed Ali (International Journal of Innovative Research and Scientific Studies, 2025)
This research aimed to study the impact of generative AI technology, specifically ChatGPT, on the development of digital entrepreneurship skills among university students. It explores how AI technologies can be integrated into higher education to develop core digital entrepreneurship skills, including innovation, creative thinking, and entrepreneurial initiative. A quasi-experimental design was employed, involving two groups of graduate students from the College of Education at King Khalid University. The experimental group was exposed to generative AI platforms (ChatGPT), while the control group was trained using traditional educational methods. To measure the impact, assessment tools, such as the Digital Entrepreneurship Scale and the Entrepreneurial Product Scorecard, were used before and after the intervention. The results indicated significant positive differences in favor of the group that used ChatGPT, demonstrating improved digital entrepreneurship skills and the ability to create pioneering digital products. Generative AI technologies provided a conducive environment for students to systematically organize their ideas, generate innovative solutions, and effectively analyze data. This research demonstrates that the integration of generative AI platforms, such as ChatGPT, into university curricula has a positive impact on the development of digital entrepreneurship skills. These technologies also enhance students' entrepreneurial mindset and innovative capabilities, helping to bridge the gap between academic learning and the practical requirements of the digital job market. Educational institutions should therefore integrate generative AI into their curricula and provide comprehensive training for faculty and students to maximize the benefits of these technologies. In doing so, universities can better prepare students for dynamic professional environments and foster sustainable and innovative digital entrepreneurship initiatives.